a) x,y nguyên => x+4; y-8 nguyên
=> x+4; y-8\(\inƯ\left(6\right)=\left\{-6;-3;-2;-1;1;2;3;6\right\}\)
ta có bảng
x+4 | -6 | -3 | -2 | -1 | 1 | 2 | 3 | 6 |
x | -10 | -7 | -6 | -5 | -3 | -2 | -1 | 2 |
y-8 | -1 | -2 | -3 | -6 | 6 | 3 | 2 | 1 |
y | 7 | 6 | 5 | 2 | 14 | 11 | 10 | 9 |
Vậy (x;y)={(-10;7);(-7;6);(-6;5);(-5;2);(-3;14);(-2;11);(-1;10);(2;9)}
b) 2x+xy+3y+6=10
<=> x(2+y)+3(y+2)=10
<=> (y+2)(x+3)=10
x,y nguyên => y+2; x+3 nguyên
=> y+2; x+3\(\in\)Ư(10)={-10;-5;-2;-1;1;2;5;10}
ta có bảng
x+3 | -10 | -5 | -2 | -1 | 1 | 2 | 5 | 10 |
x | -13 | -8 | -5 | -4 | -2 | -1 | 2 | 7 |
y+2 | -1 | -2 | -5 | -10 | 10 | 5 | 2 | 1 |
y | -3 | -4 | -7 | -12 | 8 | 3 | 0 | -1 |